Performance Optimization of a Petrochemical Cooling Tower via Fill Replacement: Cleanflow vs Cleanflow Plus - Demas Ahmad Resha Putra Hidayat; Berkah Fajar Tamtomo Kiono; Sri Widodo Agung Suedy (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
This study investigates the performance improvement of an induced draft, counterflow cooling tower after replacing the existing Cleanflow fill with Cleanflow Plus. One cell (E) was upgraded while four cells (A–D) served as the baseline under CTI ATC-105 procedures. Measurements included outlet temperature, wet-bulb temperature, circulation flow, and fan power. Results show that Cell E achieved a higher cooling range (9.20°C vs. 8.63°C average) and a lower approach (6.29°C vs. 6.87°C average). Heat-transfer capacity increased from 37.12 MW average to 39.60 MW (+6.68%). Tower capability improved from 89.00% average to 94.47% (+5.47% absolute, +6.1% relative). Number of Transfer Units (NTU) increased significantly from 2.341 to 2.889 units (+23.4%), and effectiveness improved from 71.5% to 75.9% (+6.1%). Evaporation increased from 1.21% to 1.29% (6.6%), while electrical fan power was 149.65 kW (+2.4% relative to baseline). These enhancements are attributed to the higher specific surface area (140.7 m²/m³ vs. 127.0 m²/m³, +10.8%) and improved wettability of Cleanflow Plus fill. The findings support phased implementation and further optimization across remaining cells.